Towards an agnotology of policy studies: identifying, understanding and addressing knowledge limitations in real world policymaking. (2nd February 2023) - Howlett, Michael
Abstract : Background: This comment responds to points raised in Hannah et al (2023) . Aims and objectives: The commentary frames the Hannah et al discussion within other recent moves in the policy field to take 'non-knowledge' more seriously. Methods: The commentary situates the Hannah et al discussion within the traditional literature on knowledge utilisation in the public policy literature. Findings: It is argued that while the Hannah et al article is an advance in thinking in the field it does not deal adequately with earlier efforts and findings in the literature. Discussion and conclusion: More work towards 'An agnotology of the policy studies' is needed.